Posterior Reversible Encephalopathy Syndrome in Pediatric Hematologic- Oncologic Disease: Literature Review and Case Presentation - Thaghi ARZANIAN, Mohammad; SHAMSIAN*, Bibi Shahin; KARIMZADEH, Parvaneh; KAJIYAZDI, Mohammad; MALEK, Fatima; HAMMOUD, Mohammad (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Arzanian MT, Shamsian BSh, Karimzadeh P, Kajiyazdi M, Malek F, Hammoud M. Posterior Reversible Encephalopathy Syndrome in Pediatric Hematologic-Oncologic Disease: Literature Review and Case Presentation. Iran J Child Neurol. 2014 Spring 8(2):1-10. Objective Posterior reversible encephalopathy syndrome (PRES) is a cliniconeuroradiological disease entity, which is represented by characteristic magnetic resonance imaging (MRI) findings of subcortical/cortical hyperintensity in T2-weighted sequences. It is more often seen in parietaloccipital lobes, and is accompanied by clinical neurological changes. PRES is a rare central nervous system (CNS) complication in patients with childhood hematologic-oncologic disese and shows very different neurological symptoms between patients, ranging from numbness of extremities to generalized seizure. In this article, we will review PRES presentation in hematologic-oncologic patients. Then, we will present our patient, a 7-year-old boy with Evans syndrome on treatment with cyclosporine, mycophenolate mofetil (MMF) and prednisone, with seizure episodes and MRI finding in favour of PRES. References 1. De Laat P, Te Winkel ML, Devos AS, Catsman-Berrevoets CE, Pieters R, van den Heuvel-Eibrink MM. Posterior reversible encephalopathy syndrome in childhood cancer. Ann Oncol 2011;22(2):472-8. 2. Siebert E, Spors B, Bohner G, Endres M, LimanTG. Posterior reversible encephalopathy syndrome in children: radiological and clinical findings - a retrospective analysis of a German tertiary care center. Eur J Paediatr Neurol 2013;17(2):169-75. 3. Lucchini G, Grioni D, Colombini A, Contri M, De Grandi C, Rovelli A, et al. Encephalopathy Syndrome in Children With Hemato-Oncological Disorders Is Not Always Posterior and Reversible. Pediatr Blood Cancer 2008;51:629–33. 4. Kim SJ, Im SA, Lee JW, Chung NG, Cho B, Kim HK. Predisposing Factors of Posterior Reversible Encephalopathy Syndrome in Acute Childhood Leukemia. Pediatr Neurol 2012;47(6):436-42. 5. Endo A, Fuchigami T, Hasegawa M, Hashimoto K, Fujita Y, Inamo Y , et al. Posteriorreversible encephalopathy syndrome in childhood: report of four cases and review of the literature. Pediatr Emerg Care 2012;28(2):153-7. 6. Won SC, Kwon SY, Han JW, Choi SY, Lyu CJ. Posterior Reversible Encephalopathy Syndrome in Childhood with Hematologic/Oncologic Diseases. J Pediatr Hematol Oncol 2009;31(7):505-8. 7. Legriel S, Pico F, Azoulay E. Understanding Posterior Reversible Encephalopathy Syndrome. Annual update in intensive care and emergency medicine. Springer; 2011.P.631-653. 8. Malbora B, Avcı Z, Donmez F, Alioğlu B, Alehan F, Alehan F, et al. Posterior reversible leukoencephalopathy syndrome in children with hematologic disorders. Turk J Hematol 2010;27(3):168-76. 9. Komur M, Delibas A, Arslankoylu AE, Okuyaz C, Kara E.. Recurrent and atypical posterior reversible encephalopathy syndrome in a child with hypertension. Ann Indian Acad Neurol 2012;15(3):208-10. 10. Dzudie A, Boissonnat P, Roussoulieres A, Cakmak, Mosbah K, Bejui FT, et al. Cyclosporine-Related Posterior Reversible Encephalopathy Syndrome After Heart Transplantation: Should We Withdraw or Reduce Cyclosporine?: Case Reports. Transplant Proc 2009;41(2):716-20. 11. Fuchigami T, Inamo Y, Hashimoto K, Yoshino Y, Abe O, Ishikawa T, et al. Henoch-schönlein purpura complicated by reversible posterior leukoencephalopathy syndrome. Pediatr Emerg Care 2010;26(8):583-5. 12. Incecik F, Hergüner MO, Altunbasak S, Erbey F, Leblebisatan G. Evaluation of nine children with reversible posterior encephalopathy syndrome. Neurol India 2009;57(4):475-8. 13. Chandramohan V, Nagarajan VP, Sathyamoorthi MS, Kumar S, Shanmugasundaram C, Periakaruppan G, et al. Posterior reversible encephalopathy syndrome in a child with autoimmune lymphoproliferative syndrome: Case report and review of literature. J Pediatr Neurosci 2012;7(3):221-4. 14. Wright KL, Polito MH, French AE. Posterior Reversible Encephalopathy Syndrome: A Case Study. Am J Nurs 2012;112(5):36-40. 15. Pedraza R, Marik PE, Varon J. Posterior Reversible Encephalopathy Syndrome: A Review.Crit Care & Shock 2009;12:135-43. 16. Morris EB, Laningham FH, Sandlund JT, Khan RB. Posterior reversible encephalopathy syndrome in children with cancer. Pediatr Blood Cancer 2007;48(2):152-9.